New students' perception of Online Learning during COVID-19: A case study at Telkom University - Wulan, Roro Retno; Kosasih, Deny Poniman; Nugraha, Hari Din (JESS (Journal of Educational Social Studies), 2021)
The impact of covid-19 has caused learning methods to change to online learning. The purpose of this study was to measure new students' perceptions of online learning. This study uses survey methods and data collection in the form of an instrument with a Likert scale. The purposive sampling technique was chosen with the criteria of new students from the class of 2020 with a sample of 132 respondents. Analysis of quantitative data using descriptive statistics and qualitative data using summary analysis of the results. Furthermore, the triangulation process method was used to combine quantitative data and qualitative data. The results showed that new students did not experience difficulties in carrying out online learning. The majority of FIK students use CeoLMS. The theory and assistance courses are subjects that are considered difficult by students, but the material presented by the student lecturers is satisfied. The obstacle that often occurs is signal stability, but the effectiveness of online learning can run well, although there must be several aspects that must be improved. The implications of this research can be used as a basis for evaluating learning so that FIK can improve the quality of online learning in the next academic year.